The Relationship Between Smartphone Addiction and Sleep Quality in Youth of GMIM “Eben Haezar” Kaaten Congregation - Greita Marya Selina Timpal (International Journal of Health and Medicine, 2024)
Sleep is a vital process for human recovery, occurring predominantly during rest. High-quality sleep is essential for the recovery process, helping to alleviate excessive fatigue, while poor sleep quality can lead to reduced immunity. One significant issue affecting young people today is sleep quality, which is influenced by various factors, including smartphone use. This study aimed to investigate the relationship between smartphone addiction and sleep quality among the youth of the GMIM "Eben Haezar" Kaaten. Conducted in August 2024, this cross-sectional study included all 173 youth registered in the GMIM Youth SIT, with a research sample consisting of 63 respondents. The study variables were smartphone addiction and sleep quality, analyzed using univariate and bivariate methods. Results showed that 36 respondents (57.1%) experienced a high level of smartphone addiction, while 28 respondents (44.4%) reported poor sleep quality. The study concluded a significant relationship between smartphone addiction and sleep quality, with a p-value of 0.010 and a significance level of α = 0.05.